Spectropolarimetry of Type II supernovae: I. Sample, observational data, and interstellar polarization - Nagao Takashi; Mattila Seppo; Kotak Rubina; Kuncarayakti Hanindyo (EDP Sciences, 2025)
We investigate the polarization spectra of hydrogen-rich core-collapse supernovae (Type II SNe). The polarization signal from SNe contains two independent components: intrinsic SN polarization and interstellar polarization (ISP). From these components, we can study the SN explosion geometry and the dust properties in their host galaxies or in the Milky Way. In this first paper, we employ a newly improved method to investigate the properties of the ISP components of 11 well-observed Type II SNe. Our analyses revealed that 10 of these 11 SNe showed a steady ISP component with a polarization degree of .1.0%, while one SN was consistent with zero ISP. As for the wavelength dependence, SN 2001dh (and possibly SN 2012aw) showed a non-Milky-Way-like ISP likely originating from the interstellar dust in their respective host galaxies: their polarization maxima were located at short wavelengths (.4000 Å). Similar results have been obtained previously for highly reddened SNe. The majority of the SNe in our sample had uncertainties in the wavelength dependence of their ISP components that were too large for further consideration. Our work demonstrates that further investigation of the ISP component of the SN polarization, by applying this method to a larger SN sample, can provide new opportunities to study interstellar dust properties in external galaxies.